(untitled) (Bangladesh Veterinarian, 2010)
The physical and chemical qualities of mozzarella cheese prepared from cow and buffalo milk were evaluated by a panel of judges (flavour and taste, body and texture, finish and colour) and by chemical tests (acidity, pH, fat, protein, lactose and ash). The flavour and taste, finish and colour of cow cheese were not significantly different from those of buffalo cheese. Fat, protein, lactose and ash content of cow cheese were significantly higher than those of buffalo cheese. (Bangl. vet. 2010. Vol. 27, No. 1, 36 – 42) DOI: 10.3329/bvet.v27i1.5913